Efficient distributed reachability querying of massive temporal graphs - ZHANG, Tianming (Institutional Knowledge at Singapore Management University, 2019)
Reachability computation is a fundamental graph functionality with a wide range of applications. In spite of this, little work has as yet been done on efficient reachability queries over temporal graphs, which are used extensively to model time-varying networks, such as communication networks, social networks, and transportation schedule networks. Moreover, we are faced with increasingly large real-world temporal networks that may be distributed across multiple data centers. This state of affairs motivates the paper's study of efficient reachability queries on distributed temporal graphs. We propose an efficient index, called Temporal Vertex Labeling (TVL), which is a labeling scheme for distributed temporal graphs. We also present algorithms that exploit TVL to achieve efficient support for distributed reachability querying over temporal graphs in Pregel-like systems. The algorithms exploit several optimizations that hinge upon non-trivial lemmas. Extensive experiments using massive real and synthetic temporal graphs are conducted to provide detailed insight into the efficiency and scalability of the proposed methods, covering both index construction and query processing. Compared with the state-of-the-art methods, the TVL based query algorithms are capable of up to an order of magnitude speedup with lower index construction overhead.